2011
DOI: 10.5194/acp-11-8447-2011
|View full text |Cite
|
Sign up to set email alerts
|

New particle formation infrequently observed in Himalayan foothills – why?

Abstract: Abstract.A fraction of the Himalayan aerosols originate from secondary sources, which are currently poorly quantified. To clarify the climatic importance of regional secondary particle formation in the Himalayas, data from 2005 to 2010 of continuous aerosol measurements at a highaltitude (2180 m) Indian Himalayan site, Mukteshwar, were analyzed. For this period, the days were classified, and the particle formation and growth rates were calculated for clear new particle formation (NPF) event days. The NPF event… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 64 publications
7
46
0
Order By: Relevance
“…GR values of similar magnitudes have been reported in the literature from long-term measurements from various high-altitude sites (e.g. Venzac et al, 2008;Boulon et al, 2010;Neitola et al, 2011;Yli-Juuti et al, 2011).…”
supporting
confidence: 64%
“…GR values of similar magnitudes have been reported in the literature from long-term measurements from various high-altitude sites (e.g. Venzac et al, 2008;Boulon et al, 2010;Neitola et al, 2011;Yli-Juuti et al, 2011).…”
supporting
confidence: 64%
“…Also the reduced vertical mixing of the lower atmosphere at lower temperature during winter might cause the depletion of the precursor gases and increase the condensation sink. A high background of larger particulate matter also acts as a condensation sink for the nucleating vapours and initially formed nm-sized particles (Neitola et al, 2011). We observed higher fine mode aerosol (PM 2.5 ) concentration than coarse mode (PM of diameter larger than 2.5 microns) aerosol over the same study location in the year of 2005 (Chatterjee et al, 2010) and 2008 (Chatterjee et al, 2012) throughout the entire dry season.…”
Section: Factors Controlling Ultrafine Aerosol Formationmentioning
confidence: 52%
“…In Puy de Dôme mount the maximum frequency of events was found during early spring and early autumn (Boulon et al, 2011). In the Nepal Himalayas these events were observed in the monsoon (July-September) and post-monsoon (October-December) seasons (∼ 50 %), whereas in the Indian Himalayas they occur in spring (∼ 80 % from March to June; Neitola et al, 2011). In the upper plateau of East Antarctica, Järvinen et al (2013) reported that these events take place more often during summer.…”
Section: Classification Of Episodesmentioning
confidence: 99%
“…in the Nepal Himalayas (∼ 43 %; Venzac et al, 2008) and in Puy de Dôme (∼ 38 %; Manninen et al, 2010), but higher than those observed at 2180 m a.s.l. in the Indian Himalayas (∼ 11 %; Neitola et al, 2011) and at 3580 m a.s.l. in the Swiss Alps (∼ 20 %; Jungfraujoch; Boulon et al, 2010;Manninen et al, 2010).…”
Section: Classification Of Episodesmentioning
confidence: 99%